The Adopted Bequest in Islamic Law - shahid chamran/ Haitham muzhir Mohi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Adopted’s heritage social jurisprudence research in Islamic Sharia He is entitled to an amount of the estate not exceeding one third of the estate of the adopter, as all agreed not to prove his true filiation so that the lineages would not be mixed, and it would result in the analysis of what was forbidden and the prohibition of what was permitted. It also shows how important and dangerous this issue is from its various social and legal dimensions. DOI /10.54633/2333-021-042-003